Правова держава: гострі кути на шляху від концептуальної моделі до реальності - Тертишник, В.М. (№3, 2007)
The main principle of constitutional state development are reviewed. The ways of legislation improvement are analyzed. Such crucial problems as optimization of executive and reformation of legislative branches of as well as provision of legality in the country are investigated. The necessity of judicial reform and new Constitution approval is substantiated.